Macro-encapsulation of metallic phase change material using cylindrical-type ceramic containers for high-temperature thermal energy storage. (15th May 2016) - Fukahori, Ryo; Nomura, Takahiro; Zhu, Chunyu; Sheng, Nan; Okinaka, Noriyuki; Akiyama, Tomohiro
Highlights: Macro-encapsulation of metallic phase change material (PCM) using cylindrical-type Al2 O3 containers was proposed. Al–25 wt%Si was used as PCM. Al film was used as a seal-material for the encapsulation. The PCM was completely encapsulated by Al2 O3 containers with the Al film. The prepared PCM capsule has excellent cyclic durability. Abstract: High-temperature heat storage is of growing importance for advanced solar energy utilization and waste heat recovery systems. Latent heat storage technology using alloys as phase change materials (PCM) is a promising option since it can achieve a thermal energy storage system with high heat storage density and high heat exchange rate because of the large latent heat and high thermal conductivity of metallic PCMs. Encapsulation of PCM is essential for its successful use, however, the encapsulation is very difficult owing to the high corrosivity of the metallic PCM and its volume expansion during the solid–liquid phase change. So far, the technology for encapsulating metallic PCMs has not been achieved. This study proposes the use of ceramic containers comprising a cap and a cup for macro-encapsulation of metallic PCMs, and a sealing method of the containers to endure the thermal stress from volume expansion during the phase change. The resulting PCM capsule has excellent corrosive resistance and cycling performance.